Automated line-clearing chest tubes reduce postoperative pain and atrial fibrillation after cardiac surgeryCentral MessagePerspective - Elbert E. Heng, MD; Oluwatomisin Obafemi, MD; Danielle Mullis, BS; Alyssa Garrison, MS; Hanjay Wang, MD; Jack H. Boyd, MD (JTCVS Open)
Objective: Recent advancements in chest tube technologies have gained interest for their ability to enhance postoperative recovery via reduction of retained blood syndrome after cardiothoracic surgery. The present study investigates the effect of the Centese Thoraguard automated line-clearance chest tube system on postoperative pain and recovery after cardiac surgery. Methods: This was a single-center retrospective review of 1771 adult patients undergoing nonemergency cardiac surgery between January 2021 and December 2022. Perioperative data were analyzed in 184 patients undergoing surgery with Thoraguard automated clearance chest tubes and 1587 patients with conventional chest tubes. Postoperative outcomes were compared in a propensity-matched cohort of 133 patient pairs with similar preoperative characteristics. Results: Patients undergoing cardiac surgery with automated clearance chest tubes demonstrated significant reductions in pain scores (0-10) compared with conventional chest tubes on the third postoperative day (5 vs 6, P = .02) and at hospital discharge (0 vs 3, P = .04). Automated clearance chest tubes were associated with a shorter time on the ventilator (5.3 vs 5.8 hours, P < .001). There was a significant reduction in postoperative atrial fibrillation (18.1% vs 30.8%, P = .02) in patients receiving automated clearance chest tubes. There were no significant differences in mortality, myocardial infarction, or stroke between automated line-clearing and conventional chest tubes. Conclusions: The use of the Thoraguard automated line-clearing chest tube system in routine cardiac surgery was associated with improved postoperative pain control, decreased ventilator duration, and decreased postoperative atrial fibrillation without increased morbidity or mortality.